Inherited crustal deformation along the East Gondwana margin revealed by seismic anisotropy tomography - Pilia, S; Arroucau, P; Rawlinson, N; Reading, AM; Cayley, RA (Wiley, 2016)
The mechanisms of continental growth are a crucial part of plate tectonic theory, yet a clear understanding of the processes involved remains elusive. Here we determine seismic Rayleigh wave phase anisotropy variations in the crust beneath the southern Tasmanides of Australia, a Paleozoic accretionary margin. Our results reveal a complex, thick-skinned pervasive deformation that was driven by the tectonic interaction between the proto-Pacific Ocean and the ancient eastern margin of Gondwana. Stress-induced effects triggered by the collision and entrainment of a microcontinent into the active subduction zone are evident in the anisotropy signature. The paleofracturing trend of failed rifting between Australia and Antarctica is also recorded in the anisotropy pattern as well as a tightly curved feature in central Tasmania. The observed patterns of anisotropy correlate well with recent geodynamic and kinematic models of the Tasmanides and provide a platform from which the spatial extent of deformational domains can be refined.